NLRP3 Inflammasome Activation: A Therapeutic Target for Cerebral Ischemia–Reperfusion Injury - Wang, Lixia; Ren, Wei; Wu, Qingjuan; Liu, Tianzhu; Wei, Ying; Ding, Jiru; Zhou, Chen; Xu, Houping; Yang, Sijin (Frontiers in Molecular Neuroscience, 2022)
Millions of patients are suffering from ischemic stroke, it is urgent to figure out the pathogenesis of cerebral ischemia–reperfusion (I/R) injury in order to find an effective cure. After I/R injury, pro-inflammatory cytokines especially interleukin-1β (IL-1β) upregulates in ischemic brain cells, such as microglia and neuron. In order to ameliorate the inflammation after cerebral I/R injury, NOD, LRR and pyrin domain-containing protein 3 (NLRP3) inflammasome is well-investigated. NLRP3 inflammasomes are complicated protein complexes that are activated by endogenous and exogenous danger signals to participate in inflammatory response. The assembly and activation of NLRP3 inflammasome leads to the caspase-1-dependent release of pro-inflammatory cytokines IL-1β and IL-18. Furthermore, pyroptosis is a pro-inflammatory cell death that occurs in a dependent manner of NLRP3 inflammasomes after cerebral I/R injury. In this review, we summarize the assembly and activation of NLRP3 inflammasome, moreover, we also conclude the pivotal role of NLRP3 inflammasome and inhibitors which targeting for NLRP3 inflammasome in cerebral I/R injury.